Deconstructed Trustee Theory: Disentangling Trust in Body and Identity in Multi-Robot Distributed Systems - Williams, Tom; Ayers, Daniel; Kaufman, Camille; Serrano, Jon; Roy, Sayanti (2021 16th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2021)
This paper introduces and justifies (through an n=210 online human subject study) Deconstructed Trustee Theory, a theory of human robot trust that factors the representation of trustee into robot body and robot identity in order to differentially model perceived trustworthiness of robot body and identity. This theory predicts (a) that different levels of trustworthiness can be attributed to a robot body and a robot identity, (b) that divergence between levels of perceived trustworthiness of body and identity may be effected by communication policies that reveal the potential for phenomena such as re-embodiment, co-embodiment, and agent migration in multi-robot systems, and (c) that perceived trustworthiness of body and identity may further diverge and be refined through moral cognitive processes triggered on observation of blameworthy actions. CCS CONCEPTS * Human-centered computing \rightarrowUser studies; Natural language interfaces; * Computer systems organization \rightarrowRobotics;